Helminths are Positively associated with Atopy and Wheeze in Ugandan Fishing Communities: Results from a Cross-Sectional Survey - Webb, E. L.; Nampijja, M.; Kaweesa, J.; Kizindo, R.; Namutebi, M.; Nakazibwe, E.; Oduru, G.; Kabubi, P.; Kabagenyi, J.; Nkurunungi, G.; Kizito, D.; Muhangi, L.; et al. (Allergy, 2016)
Parasitic helminths are potent immunomodulators and chronic infections may protect against allergy-related disease and atopy. We conducted a cross-sectional survey to test the hypothesis that in heavily helminth-exposed fishing villages on Lake Victoria, Uganda, helminth infections would be inversely associated with allergy-related conditions. A household survey was conducted as baseline to an anthelminthic intervention trial. Outcomes were reported wheeze in last year, atopy assessed both by skin prick test (SPT) and by the measurement of allergen-specific IgE to dust mites and cockroach in plasma. Helminth infections were ascertained by stool, urine and haemoparasitology. Associations were examined using multivariable regression. Two thousand three hundred and sixteen individuals were surveyed. Prevalence of reported wheeze was 2% in under-fives and 5% in participants ≥5 years; 19% had a positive SPT; median Dermatophagoides-specific IgE and cockroach-specific IgE were 1440 and 220 ng/ml, respectively. S. mansoni, N. americanus, S. stercoralis, T. trichiura, M. perstans and A. lumbricoides prevalence was estimated as 51%, 22%, 12%, 10%, 2% and 1%, respectively. S. mansoni was positively associated with Dermatophagoides-specific IgE [adjusted geometric mean ratio (aGMR) (95% confidence interval) 1.64 (1.23, 2.18)]; T. trichiura with SPT [adjusted odds ratio (aOR) 2.08 (1.38, 3.15)]; M. perstans with cockroach-specific IgE [aGMR 2.37 (1.39, 4.06)], A. lumbricoides with wheeze in participants ≥5 years [aOR 6.36 (1.10, 36.63)] and with Dermatophagoides-specific IgE [aGMR 2.34 (1.11, 4.95)]. No inverse associations were observed. Contrary to our hypothesis, we found little evidence of an inverse relationship between helminths and allergy-related outcomes, but strong evidence that individuals with certain helminths were more prone to atopy in this setting.
Keywords: Helminths; Atopy and Wheeze; Fishing communities